Chemical reduction dependent dielectric properties and dielectric loss mechanism of reduced graphene oxide. (February 2018) - Kuang, Boya; Song, Weili; Ning, Mingqiang; Li, Jingbo; Zhao, Zhengjing; Guo, Deyu; Cao, Maosheng; Jin, Haibo
Abstract: Reduced Graphene Oxide (rGO) is expected to be the most promising candidate for high-efficiency electromagnetic wave absorption materials. However, its defect-related dielectric loss mechanism has not been clarified up to date, especially when it comes to the pure rGO system. Here, the rGO with controllable reduction degree is prepared. The oxygen-containing functional groups are regularly removed from rGO during reduction. Accompanying with the decrease of oxygen-containing functional groups, the content of lattice-defects in rGO is increased with increasing reduction degree of rGO. The dielectric and microwave absorption properties of rGO with different reduction degrees are investigated over 2–18 GHz. Compared to the GO, rGO exhibits obvious dielectric relaxation behaviors with a relaxation peak at ∼10 GHz. The dielectric relaxation of rGO is enhanced by increasing reduction degree of rGO. The experimental results evidence that the enhanced dielectric relaxation behavior originates from the increased vacancy defect dipoles in rGO generated through chemical reduction, and rule out the contribution of oxygen-containing functional groups to the dielectric relaxation. This work reveals the mechanism of defect-related dielectric relaxation of rGO, which may contribute to the correct understanding of dielectric loss of carbon-based materials for designing and/or modifying carbon-based microwave attenuation materials. Graphical abstract: Image 1